El estrés laboral y el desempeño del personal administrativo del Gobierno Autónomo Descentralizado Municipal del Cantón Gonzanamá periodo abril 2021- marzo 2022 - Cuenca Rivas, María José (2023)
The objective of this research work was to determine how work stress influences the performance of the administrative personnel of the Autonomous Decentralized Municipal Government of Canton Gonzanamá, period April 2021 - March 2022, therefore, the level of stress of the administrative personnel was diagnosed; the factors that influence performance were identified; and an improvement plan was designed to reduce work stress and optimize performance. The research was developed from a mixed, non-experimental approach, and was established as descriptive, deductive, inductive, analytical and synthetic. The techniques used were: a survey and interview applied to 53 employees; the OIT-OMS work stress scale questionnaire based on the theoretical model of stress of Ivancevich and Mattteson (1989) was used as an instrument. Questions were elaborated to identify performance factors through the theoretical model of work performance of Cardy and Dobbins (1994), therefore a semi-structured interview was conducted with the highest authorities such as the Mayor and the Chief of Human Resources; the results obtained showed a high level of stress, therefore an improvement plan was designed for the benefit of the personnel and the entity. The method used to determine the relationship between the study variables was Fisher's exact test, which was used to reject the null hypothesis (Ho) "Job stress factors ARE independent of performance factors" and to accept the alternative hypothesis (Ha) "Job stress factors ARE NOT independent of performance factors". Thus determining that job stress does influence the performance of the administrative personnel of the GAD of Gonzanamá.